Isolation and Characterization of Pseudomonas sp. HX1, Streptomyces luteogriseus HR40, and Streptomyces flavofungini HR77 as Promising Biocontrol Agents Against Verticillium Wilt in Hops Affected by Verticillium nonalfalfae - Seyedehtannaz Ghoreshizadeh; Carla Calvo-Peña; Marina Ruiz-Muñoz; Maja Dobrajc; Sebastjan Radišek; Juan José R. Coque; Rebeca Cobos (Horticulturae)
Verticillium spp. are soil-borne fungal pathogens capable of infecting over 400 plant species via their root systems, with each species demonstrating a distinct host range. The primary host of Verticillium nonalfalfae is the hop plant (Humulus lupulus), which becomes affected by Verticillium wilt and, in severe cases, dieback. A dual screening approach was employed to isolate Streptomycetes as potential biocontrol agents from the hop root systems alongside other bacterial species from hop xylem. Three Pseudomonas strains from the xylem and three Streptomyces strains from the roots were selected based on their in vitro antifungal activity against Verticillium dahliae and/or V. nonalfalfae. Their potential for controlling Verticillium wilt was further assessed through in planta assays conducted under greenhouse conditions. The results demonstrated that Pseudomonas sp. HX1, Streptomyces luteogriseus HR40, and Streptomyces flavofungini HR77 significantly reduced the disease severity index by 32.56% compared to artificially infected control plants. In contrast, the commercial biocontrol product Serenade® ASO, containing Bacillus amyloliquefaciens QST 713, achieved a reduction of 13.96%. These findings underscore the potential of the selected bacterial strains as promising candidates for the biological control of Verticillium wilt in hops affected by V. nonalfalfae.